1993
DOI: 10.1111/j.2042-3306.1993.tb02989.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of ossification of the collateral cartilages of the third phalanx in Finnhorses

Abstract: Summary Of 462 Finnhorses (age 1–20 years) evaluated and graded (scale 0–5) radiographically for ossification of the collateral cartilages of the 3rd phalanx of the front feet, 22.9% were totally free from sidebones (Grade 0), and 49.1% had minimal or mild ossification (Grade 1 or 2) at the base of 1 or more of the cartilages. Moderate ossification (Grade 3) was present in 10.2% of the horses, whereas ossification was advanced (Grade 4) or extensive (Grade 5) in 17.8%. In most horses >1 cartilage was affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 2 publications
(6 reference statements)
11
61
1
Order By: Relevance
“…Unless fractured, OUC has been questioned as an obvious cause of lameness in several studies [27,28], but it has been suggested by Ruohoniemi et al [8] that it may have an impact on gait at high speed. When grouped together, horses with OUC of grade 1 and 2, according to the NS, had a tendency for more frequent records of irregular trot than horses without OUC or OUC of grade 3 ( P  = 0.08).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unless fractured, OUC has been questioned as an obvious cause of lameness in several studies [27,28], but it has been suggested by Ruohoniemi et al [8] that it may have an impact on gait at high speed. When grouped together, horses with OUC of grade 1 and 2, according to the NS, had a tendency for more frequent records of irregular trot than horses without OUC or OUC of grade 3 ( P  = 0.08).…”
Section: Discussionmentioning
confidence: 99%
“…For 95% of the horses, conventional film and a cassette with intensifying screens were used, while digital radiography was used for the remaining 5%. All radiographs were blind-coded and evaluated twice by the same person (OW) using both the scale of Ruohoniemi et al [5] and a new scale (NS) in which the navicular bone and the palmar level of the distal interphalangeal joint were excluded as references (Figure 1). The cartilage with the highest grade of ossification, including both the left and right front feet, determined the total score for an individual horse.
Figure 1 OUC grading systems.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different evaluation scales have been used in radiological studies of OUC in Ardenner horses [15], Finnhorses [8], Warmbloods [16] and Brazilian Showjumpers [7], but the long term impact of extensive ossification on performance has been poorly evaluated. Official Swedish statutes on horse breeding exclude stallions of all breeds if OUC is severe or present early in life [17].…”
Section: Introductionmentioning
confidence: 99%